Impact of saline valorization in contaminated municipal wastewater on the treatment performance and bacterial community dynamics of a membrane bioreactor - Ittisupornrat S. (2023)
Background: Due to salt intrusion and the improper use of seawater for cleaning and flushing in food shops along coastal regions, the aerobic biological wastewater treatment process may have an adverse effect on treatment performance. This study demonstrates membrane bioreactor (MBR) performance for treating saline-contaminated municipal wastewater. The aim of this study is to determine how much salt affects the efficiency of the process and how the functional bacterial community evolves in an MBR for treating actual municipal wastewater. Results: An MBR was applied for actual municipal wastewater treatment by increasing the NaCl concentration from 0 to 20 g L−1 with a hydraulic retention time of 12 h and complete sludge retention. High removal efficiencies of chemical oxygen demand (COD) (ranging from 80.3 to 82.8 mgL−1) and ammonium-N (ranging from 40.8 to 44.4 mgL−1) were found at salinity concentrations of up to 7.8 ± 0.8 g L−1. However, the removal efficiency of COD was below 50% at high salinity concentrations of 17.9 ± 1.3 g L−1, whereas the removal rate of ammonium-N had slightly changed with the value of 90%. In terms of bacterial composition, the largest dominant bacterial communities were Proteobacteria and Planctomycetota, both of which may be the predominant halotolerant/halophilic bacteria group. Additionally, Rhizobiales, Planctomycetales, Pirellulales, and Gemmatales (all of which are members of these phyla) were increased, suggesting that they played an important role in the biodegradation process. Conclusion: The MBR operation showed a good performance for treating municipal wastewater with high salinity concentrations, with a salt tolerance threshold of 7.8 g L−1. The experimental results indicate that the MBR system can be applied for treating municipal wastewater that is occasionally contaminated with seawater. © 2022 Society of Chemical Industry (SCI).